Analysis Of Marketing Communications in Building Brand Awareness at Distro Madman Wear Sumedang - Cut Wahidanti Zahrahast; Aa Kartiwa; Yayat Ginanjar (SINTESA, 2022)
This study aims to find out about Marketing Communication in Building Brand Awareness at Distro Madman Wear Sumedang. This study uses a qualitative research method with a descriptive approach. The sampling technique used in this research is a purvose sampling technique with research informants, owners and leaders of distributions and consumers of Madman Wear Sumedang distributions. The research was conducted using the Miles Huberman model with steps including Data Reduction, Data Presentation, and Drawing Conclusions. The results of the study found that Marketing Communication in Building Brand Awareness at Distro Madman Wear Sumedang was not optimal based on the assessment of the dimensions of Marketing Communication which included (advertising, sales promotion, direct marketing, public relations and word of mouth) and Brand Awareness covering (top of mind, brand recall, brand recognition, unaware of brand). The conclusion of this study for the Distro Madman Wear Sumedang is to further develop product innovation and maintain brand image and intensify marketing activities so that the Madman Wear Sumedang distribution brand can be embedded in the minds of consumers.